A fast tool for ICRH + NBI modelling within the EU-IM framework. (12th April 2021) - Van Eester, Dirk; Lerche, E.A.; Huynh, Ph.; Johnson, T.; ,; ,
Abstract : Most if not all tokamak heating scenarios involve multiple ion populations being heated simultaneously. To allow the simulation of various aspects of physics dynamics determining the characteristics of operational scenarios in a flexible way, speedy yet sufficiently accurate models are needed, and they should be connected to each other via a 'backbone'. Under the umbrella of EUROfusion's Integrated Modelling efforts, such a structure is provided. The present paper focuses on one physics aspect: auxiliary heating. After solving the wave equation or beam source equation, this requires solving a set of coupled Fokker–Planck equations for the various populations involved. The adopted modules – enabling accounting for the Coulomb collisional interaction of several non-Maxwellian (minority, majority and beam) populations – are discussed and a practical example of their use is provided: the JET 'baseline' scenario heating a minority of ${}^3He$ ions in a balanced D $+$ T mix heated by D and T neutral beams.